2003
DOI: 10.1073/pnas.1633612100
|View full text |Cite
|
Sign up to set email alerts
|

The lipoxygenase gene ALOXE3 implicated in skin differentiation encodes a hydroperoxide isomerase

Abstract: Herein we identify a logical link of the biochemistry to the genetics. eLOX3 functions as a hydroperoxide isomerase (epoxyalcohol synthase) by using the product of 12R-LOX as the preferred substrate. 12R-Hydroperoxyeicosatetraenoic acid (12R-HPETE) is converted to 8R-hydroxy-11R,12R-epoxyeicosa-5Z,9E,14Z-trienoic acid, one of the isomers of hepoxilin A 3, and to 12-ketoeicosatetraenoic acid in a 2:1 ratio. Other hydroperoxides, including 8R-HPETE, 12S-HPETE, and 15S-HPETE, as well as the 13S-and 13R-hydroperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 35 publications
5
152
0
1
Order By: Relevance
“…The antibody raised against rat 12S-LOX (HXA 3 synthase) recognized also human epidermal 12S-LOX (HXA 3 synthase). As mutated eLOX3 is still expressed at the protein level in cells [7,8], these findings suggest to us that the patient in the case study has a different ichthyosis form than that reported for NCIE patients, who showed deficiency of 12R-LOX or eLOX3 due to gene mutations [5][6][7].…”
Section: Gc-ms Analysissupporting
confidence: 53%
See 1 more Smart Citation
“…The antibody raised against rat 12S-LOX (HXA 3 synthase) recognized also human epidermal 12S-LOX (HXA 3 synthase). As mutated eLOX3 is still expressed at the protein level in cells [7,8], these findings suggest to us that the patient in the case study has a different ichthyosis form than that reported for NCIE patients, who showed deficiency of 12R-LOX or eLOX3 due to gene mutations [5][6][7].…”
Section: Gc-ms Analysissupporting
confidence: 53%
“…These authors also postulated that product of one of these enzymes (12R-LOX) may serve as substrate for the other (eLOX3), thus functioning in the same metabolic pathway [4]. Yu et al [6,7] showed that eLOX3, which does not exhibit any oxygenase activity, operates as an epoxy alcohol synthase utilizing preferably the product from 12R-LOX, termed 12R-hydroperoxyeicosa-5,8,10,14-tetraenoic acid (12R-HpETE) as substrate, thus providing for the first time a clear-cut evidence for a functional linkage of proteins 12R-LOX and eLOX3. Both proteins 12R-LOX and eLOX3 are coexpressed in tissues, and mutations in any of the two causative genes can lead to NCIE [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the deleted region contains a cluster of 3 genes involved in lipid oxygenation, two of which are epidermal lipoxygenases that are expressed primarily in the mouse skin (Boeglin et al ., 1998;Jisaka et al ., 1997;Heidt et al ., 2000). Lipoxygenases have been shown to play important biological roles in mediating adipocyte and skin differentiation, inflammatory responses, and are also expressed in human hair roots (Baer & Green, 1993;Shillabeer et al ., 1998;Furstenberger et al ., 2002;Kantarci & Van Dyke, 2003;Yu et al ., 2003;Yu et al ., 2005). Correlating to this expression pattern, we do see skin phenotypes that include reduction in dermal thickness, subcutaneous adipose layer, hair re-growth potential and skin wound healing in the p53+/m mice, indicating that the loss of these genes may be responsible for this phenotype.…”
Section: S Venkatachalam Department Of Biochemistry and Cellular Anmentioning
confidence: 99%
“…Mutations in the lipid transporter protein, ABCA12 cause defective lipid secretion into lamellar granules which then become expelled from the apical surface of keratinocytes [6] as mentioned above and lead to either LI [5] and HI [6,18] phentoypes. Lipoxygenase-3 and 12(R)-lipoxygenase are non-heme iron-containing dioxygenases expressed in the epidermis, and their exact functions are unknown [19,20]. They may be associated with lipid metabolism in the lamellar granule contents and/or intercellular lipid layers in the epidermis.…”
Section: Defective Intercellular Lipid Is the Main Idea Behind The Pamentioning
confidence: 99%